Measuring the acute cardiovascular effects of shisha smoking: a cross-sectional study. (6th May 2014) - Kadhum, Murtaza; Jaffery, Ali; Haq, Adnaan; Bacon, Jenny; Madden, Brendan
Objectives: To investigate the acute cardiovascular effects of smoking shisha. Design: A cross-sectional study was carried out in six shisha cafes. Participants smoked shisha for a period between 45 min (minimum) and 90 min (maximum). The same brand of tobacco and coal was used. Setting: London, UK. Participants: Participants were those who had ordered a shisha to smoke and consented to have their blood pressure, heart rate and carbon monoxide levels measured. Excluded subjects were those who had smoked shisha in the previous 24 h, who smoke cigarettes or who suffered from cardiorespiratory problems. Main outcome measures: Blood pressure was measured using a sphygmomanometer. Pulse was measured by palpation of the radial artery. Carbon monoxide levels were obtained via a carbon monoxide monitor. These indices were measured before the participants began to smoke shisha and after they finished or when the maximum 90 min time period was reached. Results: Mean arterial blood pressure increased from 96 mmHg to 108 mmHg ( p  < 0.001). Heart rate increased from 77 to 91 bpm ( p  < 0.001). Carbon monoxide increased from an average of 3 to 35 ppm ( p  < 0.001). A correlation analysis showed no relationship between carbon monoxide and the other indices measured. Conclusion: The acute heart rate, blood pressure and carbon monoxide levels were seen to rise significantly after smoking shisha. The weak correlation between carbon monoxide levels and the other variables suggests that carbon monoxide levels had not contributed to their significant increase.